2020
DOI: 10.1177/0093854820983848
|View full text |Cite
|
Sign up to set email alerts
|

Hate Crime Victimization and Weapon Use

Abstract: Prior research has suggested that hate crimes hurt more, in that they are more physically severe than other crimes. A separate body of research has focused on the role of weapons in exacerbating violence; yet, no research has considered the role of weapon use in bias crime victimization. Following this, this research examines the relationship between weapon use, bias motivation, and victimization in the United States. On one hand, weapons may play an important role in hate crime by exacerbating violence. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Although hate and bias crimes have been increasing in the United States in recent years (Kena & Thompson, 2021; Smith, 2021) and there is a substantial amount of evidence suggesting that hate crimes are more severe than other crimes (Iganski, 2001; Lantz & Kim, 2019; Malcom & Lantz, 2021), hate crime legislation remains a particularly divisive issue in American society. More specifically, while most Americans agree that hate crime laws are necessary, roughly one third of Americans are still unsupportive of such legislation (Steen & Cohen, 2004; see also, Cramer et al, 2017; Hart & Teeter, 1999a, 1999b).…”
Section: Discussionmentioning
confidence: 99%
“…Although hate and bias crimes have been increasing in the United States in recent years (Kena & Thompson, 2021; Smith, 2021) and there is a substantial amount of evidence suggesting that hate crimes are more severe than other crimes (Iganski, 2001; Lantz & Kim, 2019; Malcom & Lantz, 2021), hate crime legislation remains a particularly divisive issue in American society. More specifically, while most Americans agree that hate crime laws are necessary, roughly one third of Americans are still unsupportive of such legislation (Steen & Cohen, 2004; see also, Cramer et al, 2017; Hart & Teeter, 1999a, 1999b).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, research has demonstrated a relationship between experiences with racial discrimination and a number of negative mental health outcomes, including psychological distress, reduced life satisfaction, decreased self-esteem, anxiety, depression, suicidal ideation, and other mental health issues ( Gee et al, 2007 ; Hwang & Goto, 2008 ; Nadal et al, 2015 ; Padela & Heisler, 2010 ; Sue et al, 2009 ). Prior research has also suggested that hate crimes can result in severe physical trauma and negatively impact physical health as well ( Chen et al, 2020 ; Gee et al, 2007 ; Lantz & Kim, 2019 ; Malcom & Lantz, 2021 ). Given the scope of the COVID-19 pandemic, researchers should make careful efforts to better understand the specific consequences of COVID-19-related discrimination and bias if we hope to develop appropriate interventions to deal with such issues.…”
Section: Discussionmentioning
confidence: 99%
“…From a policy perspective, it is also important to consider the profound physical and mental health consequences of hate crime victimization. Hate crimes tend to be more physically severe than other crimes (e.g., Lantz & Kim, 2019; Malcom & Lantz, 2020) and more psychologically traumatic than other crimes (e.g., Herek et al, 1997). Within this context, one of the most important consequences of the disclosure of victimization is the access to resources for dealing with the victimization, including victim support services (Fisher et al, 2003).…”
Section: Discussionmentioning
confidence: 99%